Der vormoderne Allokationsprozess von Arbeit in Deutschland - Toni Pierenkemper; Michael J. Kendzia (Institute for the Study of Labor (IZA), 2010)
The paper provides a historical overview of the pre-modern allocation of work within the territory of the later Germany from the 18th until the middle of the 19th century. We explore how the social allocation of work during the feudal system took place and trace back the development of wage labor within agriculture, industry and service sector. In particular, the historical roots of the so-called 'standard employment contract' in Germany are investigated. We find that during the pre-industrial time the social organization of work occurred in various forms and that wage labor was rather a rare phenomenon in the beginning of the 19th century. Hence, a widespread and functioning labor market cannot be identified at that time. Rudimentary elements of the standard employment contract are found in the employment contract of civil servants.
Keywords: J50; J40; 330; Feudal system; pre-industrial; allocation of work; wage labor; standard employment contract; Arbeit; Allokation; Feudalismus; Arbeitsmarkt; Geschichte; Lohn; Arbeitsvertrag; Deutschland